2022
DOI: 10.1101/2022.08.03.502670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of transposable element accumulation in the non-recombining regions of mating-type chromosomes in anther-smut fungi

Abstract: Background: Transposable element (TE) activity is generally deleterious to the host fitness, so that genomes often evolve TE control mechanisms, and TE copies are purged by recombination and selection. In the absence of recombination, the number of TE insertions usually increases, but the dynamics of such TE accumulations is unknown. Results: In this study, we investigated the tempo of TE accumulation in the non-recombining genomic regions of 15 Microbotryum species, leveraging on a unique dataset of 21 indepe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 140 publications
1
18
0
Order By: Relevance
“…The structural dynamism in the SDR is likely driven by TE-mediated chromosomal rearrangements 44 , since the sex chromosome is enriched in TEs relative to the rest of the genome. As described in other systems, including mating type chromosomes in fungi 45,46 , TE accumulation was likely a consequence of the initial recombination suppression in the SDR 47 which possibly initiated a positive feedback loop between the accumulation of TEs in the sex chromosome and the subsequent rearrangement and expansion of the SDR.…”
Section: Structure and Synteny Level Of Brown Algal Sex Chromosomesmentioning
confidence: 63%
“…The structural dynamism in the SDR is likely driven by TE-mediated chromosomal rearrangements 44 , since the sex chromosome is enriched in TEs relative to the rest of the genome. As described in other systems, including mating type chromosomes in fungi 45,46 , TE accumulation was likely a consequence of the initial recombination suppression in the SDR 47 which possibly initiated a positive feedback loop between the accumulation of TEs in the sex chromosome and the subsequent rearrangement and expansion of the SDR.…”
Section: Structure and Synteny Level Of Brown Algal Sex Chromosomesmentioning
confidence: 63%
“…Addressing these knowledge gaps has long been a challenge because initial genome assemblies of rust fungi were fragmented and the structure of the MAT loci could not be assessed consistently. For example, clustering of repetitive elements around MAT loci (17,36,37) is a challenge for studying MAT loci in rust fungi with repeat-rich genomes because repetitive sequences cause gaps, fragmentation, and phase-errors in the assembled genome.…”
Section: Introductionmentioning
confidence: 99%
“…By dating retrotransposon insertions using between-copy divergence and within-copy LTR divergence in both M1400 and M6697 genomes (Fig 5C and D), we found that TEs within the inversion and around the inversion breakpoints were older than TEs farther from the breakpoints. This is expected in non-recombining regions as selection is there less efficient to purge TE insertions so that they remain there longer (Duhamel et al 2023). The date estimates of LTR element insertions (Fig 5D ) further indicated that the TE accumulation in the MAT-proximal region was as old as a few million years, confirming the age estimated based on sequence divergence between MAT-proximal haplotypes.…”
Section: Enrichment Of Transposable Elements In the Non-recombining R...mentioning
confidence: 99%